Pengaruh Opini Audit, Fee, Kesulitan Keuangan, dan Efektivitas Komite Terhadap Audit Delay - Mutiara Islamy Putri; Tumirin Tumirin (Universitas Muhammadiyah Gresik, 2022)
This study aims to determine the effect of audit opinion, fees, financial difficulties, the size of the committee's expertise, and committee meetings on audit delay. The population of this study is all companies listed on the Indonesia Stock Exchange in 2020. The total sample of this study is 40 companies. Data analysis was carried out with classical assumptions and hypothesis testing using multiple linear regression with SPSS version 23. The results showed audit opinion, audit fees, committee expertise, audit committee size had a positive effect on audit delay. Meanwhile, financial difficulties, and audit committee meetings have no effect on audit delay. The effect of the independent variable to describe the audit delay variable is 33.4% while the other 66.6% is explained by other variables outside the study.